(untitled) (Proceedings of the International Conference on Social Sciences, 2024)
The teachers’ Information and Communications Technology (ICT) knowledge and skills help them to be more efficient in performing their tasks, ensure effective learniung to students, and adhere to ICT advancements and competency. The study aimed to determine the level of ICT readiness of the 18 faculty members of the Local City College during the school year 2021-2022 based on profile: age, number of ICT training hours attended, length of service, and sex. A modified survey questionnaire was used to measure ICT readiness in terms of ICT knowledge (through Self-Administered Questionnaire) and ICT skills (through skills demonstration), which were derived from the National ICT Competency Standard of the Commission on Information and Communications Technology and the Computer Literacy Questionnaire. It made use of descriptive-quantitative and qualitative designs. The findings revealed that the faculty were knowledgeable and skilled in basic ICT. The common themes derived from the resulting discrepancy between ICT knowledge and ICT skills were wrong perceptions or assumptions, confusion on the unfamiliar/technical words/terms, and low confidence level which was associated with the random response bias. It was concluded that teachers were skilled and knowledgeable equally or similarly ready in ICT, whether they were clustered according to sex, age groups, number of ICT training hours attended, and length of service in using common computer applications in the basic skills set, namely: Word Processing, Presentation, ICT Basics, Internet Skills, Computer ethics, security, and spreadsheets. Furthermore, the study recommended an intervention program to be conducted among faculty members of the local city college to prepare teachers to be highly knowledgeable and skilled in ICT.